The 5th wave [videorecording (DVD)] - Moretz, Chloë, 1997-; Zuk, Matthew; López, Gabriela (Sony Pictures Home Entertainment, 2016)
Sixteen-year-old Cassie Sullivan is trying to survive a world devastated by the waves of an alien invasion, while trying to save her five-year-old brother Sam from a training camp that was created by the Others (the aliens).